2017
DOI: 10.1093/dnares/dsx037
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide mapping of large deletions and their population-genetic properties in dairy cattle

Abstract: Large genomic deletions are potential candidate for loss-of-function, which could be lethal as homozygote. Analysing whole genome data of 175 cattle, we report 8,480 large deletions (199 bp–773 KB) with an overall false discovery rate of 8.8%; 82% of which are novel compared with deletions in the dbVar database. Breakpoint sequence analyses revealed that majority (24 of 29 tested) of the deletions contain microhomology/homology at breakpoint, and therefore, most likely generated by microhomology-mediated end j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 72 publications
9
26
0
Order By: Relevance
“…Taken together, the studies that focused on mid-sized CNVs [62][63][64] are in line with our findings, whereas studies based on tiling oligonucleotide microarrays [65] and whole genome sequencing data [5,66], which can provide rather complete genome-wide coverage with a various size range of CNVs [4], show different results.…”
Section: Functional Impact Of Cnvrssupporting
confidence: 89%
See 3 more Smart Citations
“…Taken together, the studies that focused on mid-sized CNVs [62][63][64] are in line with our findings, whereas studies based on tiling oligonucleotide microarrays [65] and whole genome sequencing data [5,66], which can provide rather complete genome-wide coverage with a various size range of CNVs [4], show different results.…”
Section: Functional Impact Of Cnvrssupporting
confidence: 89%
“…Also, a deletion variant overlapping with ADAMTS17 was shown to be highly diverged between HOL and JER in a previous study [66]. Given that CNVR 1452 we found is a duplication locus, it might be a different mutation than the one found by Mesbah-Uddin et al [66]. Nonetheless, our and the previous findings revealed that CNVs overlapping with ADAMTS17 gene to be diverged between HOL and JER.…”
Section: Population Genetics Of Cnvrssupporting
confidence: 54%
See 2 more Smart Citations
“…These studies were based on medium-to-large size human CNVs, and rat CNVs were found from exome arrays (CNV length ranged between 5 and 256 kb). However, more recent studies, based on a finer resolution of CNVs, concluded that CNVs are biased away from genes and functional elements [5,[65][66][67].…”
Section: Functional Impact Of Cnvrsmentioning
confidence: 99%